2022
DOI: 10.2298/tsci210322002s
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of curvature effect on pressure drop of gas-liquid two-phase flow through 90 degree elbow

Abstract: Computational fluid dynamics (CFD) analysis of air-water two-phase flows was performed in a 90? vertical to horizontal elbows made of PVC with four different inside diameters (25, 50, 75, and 100 mm) with six different curvature radius to diameter ratios (R/D) 1, 2, 4, 6, 8, and 10. Pressure drops were investigated at various upstream and downstream locations using computational, experimental, empirical methods. The most effective method in investigating and determining total pressure drop of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Correspondingly, scholars have examined the various relationships between the pressure drop and the fow condition or geometry of a bend. Saber and Maree [16] found that a signifcant pressure drop occurs at higher air fow rates through a numerical model constructed for a vertical L-shaped pipe.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, scholars have examined the various relationships between the pressure drop and the fow condition or geometry of a bend. Saber and Maree [16] found that a signifcant pressure drop occurs at higher air fow rates through a numerical model constructed for a vertical L-shaped pipe.…”
Section: Introductionmentioning
confidence: 99%